Entrepreneurial factors that contribute to a business start-up among Malaysian community college students - Ooi, Yeng Keat; Hoe, Chee Hee; Ahmad, Shuhymee; Hashim, Norashidah (2014)
This study investigates the effect of entrepreneurship education on Malaysian community college students’ inclination towards entrepreneurship. The objective of this study is to examine the effect of entrepreneurship education on the Malaysian community college students’ inclination towards entrepreneurship. The sample consisted of 250 students from four community colleges who were the final year students of their diploma studies in various disciplines.A survey questionnaire was employed to elicit response concerning their entrepreneurship inclination and characteristics. The data was analysed using descriptive (for respondents’ characteristics) and regression (for the entrepreneurial factors) statistics. The results of the study showed that 50.8 per cent of the community college students would consider starting a business as their future career whilst 32.8 per cent stated that they are likely to start a business after graduation.This is mainly due to the effort taken by the community colleges in promoting entrepreneurship among students. In terms of entrepreneurial factors, role models and the role played by community colleges in promoting entrepreneurship appear to have statistically significant influence in community college students’ decision to pursue an entrepreneurial career.Hence, this study showed that community colleges and role models play a vital role in fostering and promoting entrepreneurship in order to produce more entrepreneurial-inclined graduates.Recommendations and future research are made based on the findings of the study.